The Influence of The Problem-Based Learning Model on The Learning Outcomes of Seventh-Grade Students Junior High School - Khalifah, Shela Mardha; Susanta, Agus; Sumardi, Hari; Susanto, Edi (Universitas Wiralodra, 2023)
Learning outcomes, especially mathematics, are still low both at the international and national levels. The results of the 2021 minimum competency assessment show that student achievement in Indonesia is still low. This requires educators to be more innovative in learning in class so that they can support students' thinking skills. This study aims to determine the effect of the Problem-Based Learning model on the mathematics learning outcomes of seventh-grade students of junior high school number 1 in North Bengkulu. This research is a quasi-experimental type with Nonequivalent Pretest-Posttest Control Group Design. The population in this study were all students of seventh-grade students of junior high school number 1 in North Bengkulu. The sample selection used a simple random sampling technique with class VII D as the experimental class and class VII E as the control class. Data collection was carried out using a test using the research instrument, namely the learning achievement test. Data were analyzed using the t-test statistic. The results showed that there was a significant effect of the problem-based learning model on the social arithmetic learning outcomes of seventh-grade students of Junior High School 1 in North Bengkulu.